Pengaruh Bioaspal terhadap Modulus Kekakuan Bitumen Asbuton (Dynamic Shear Rheometer dan Pendekatan Model Matematis Ullidtz) - Sihombing, Atmy Verani Rouly (Universitas Ibn Khaldun, 2026)
This study investigates the effect of bio-binder addition on the stiffness modulus of Buton asphalt (Asbuton) bitumen using the Ullidtz mathematical approach and Dynamic Shear Rheometer (DSR) testing. Asbuton B 50/30 was modified with bio-binders derived from pyrolysis of coconut shells (BTK) and rice straw (BJe). The optimum bio-binder content was determined based on penetration and softening point values comparable to Pen 60/70 asphalt as the control binder. The results indicate that 6.5% BTK and 8% BJe effectively increased penetration and reduced the softening point under RTFOT conditions, demonstrating a significant softening effect. The calculated stiffness modulus (Sbit) from the Ullidtz model and DSR measurements exhibited a consistent decreasing trend with increasing temperature (20–45°C), reflecting the viscoelastic behavior of asphalt. However, the Ullidtz approach generally underestimated stiffness values compared to DSR results, particularly at higher temperatures and for modified binders. An adjustment factor of 1.16 was applied to improve the agreement between both methods. The findings confirm that bio-binders have strong potential as sustainable modifiers to control the stiffness of Asbuton bitumen. While the Ullidtz approach provides a practical preliminary estimation, DSR testing remains more reliable for accurately characterizing the mechanistic and viscoelastic behavior of modified asphalt binders.